RELIGIUSITAS DAN KINERJA PEGAWAI SETELAH PEMBERIAN VAKSIN COVID-19 : PERAN MEDIASI WORK ENGAGEMENT - Barkhowa, Mokhammad Khukaim; Fitriyanti, Nurul; Barhaq, Vio Vanessa (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2022)
New normal life aims to improve faith and religiosity, by worshiping according to their respective beliefs. Work engagement is also the feeling of workers being comfortable with their work or organization so that faith or worship is needed to be comfortable with their work or organization. This study aims to examine how religiosity has on employee performance with work engagement as mediation for company employees in Salatiga City. The sample in this study uses the calculation with the Slovin formula with a sample of 100 employees. Sampling using simple random sampling. There are three measuring tools for data analysis in testing the hypothesis, namely Simple Regression Analysis, Multiple Regression Analysis, and Sobel Test through Classical Assumption Test, Model Goodness Test, and Validity and Reliability Test. The results of hypothesis testing are that religiosity has a positive effect on work engagement, work engagement has a positive effect on employee performance, and religiosity affects employee performance through work engagement.